Lack of association between aspirin responsiveness and seven candidate gene haplotypes in patients with symptomatic vascular disease - Kunicki, Thomas J; Williams, Shirley A; Nugent, Diane J; Harrison, Paul; Segal, Helen C; Syed, Anila; Rothwell, Peter M (Thrombosis and haemostasis, 2009)
We studied the effect of prophylactic aspirin (ASA) ingestion on platelet function in 463 patients with stroke, transient ischemic attack (TIA) or acute coronary disease (ACD), using the Platelet Function Analyzer-100 (PFA-100). We correlated ASA responsiveness with haplotypes of seven candidate genes, selected for their documented role in platelet function, namely, the genes for integrins alpha2beta1and alphaIIbbeta3 (ITGA2, ITGA2B, and ITGB3), platelet glycoproteins Ibalpha and VI (GPIBA and GP6), the purinergic receptor P2Y1 (P2RY1), and prostaglandin H synthase 1 (PTGS1 = COX1). Non-responsiveness to ASA was defined as the failure of prior ASA ingestion to prolong the PFA-100 closure time (CT) when blood was perfused through cartridges coated with collagen plus epinephrine (CEPI-CT). ASA non-responsiveness was observed in 114 of 463 patients (24.6 %), but was not associated with haplotypes of any of the seven candidate genes. There was also no association between any haplotypes and the CT when blood was perfused through cartridges coated with collagen plus ADP (CADP-CT). The ASA non-responsive cohort had significantly increased whole blood platelet counts (p = 0.03) and plasma von Willebrand Factor antigen levels (p < 0.001), which likely contributes to resistance to the inhibitory effects of ASA in the PFA-100.